PENGARUH PENGGUNAAN MEDIA ULAR TANGGA TERHADAP KECERDASAN LOGIKA MATEMATIKA ANAK USIA 5-6 TAHUN DI TK NEGERI SATU ATAP 02 LUBUK PAKAM - Siti Fadia Annisa; Juli Yanti Harahap (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The aim of this research is to determine the effect of using snakes and ladders media on mathematical logic intelligence in children aged 5-6 years at Kindergarten One Roof 02 Lubuk Pakam. The type of sample selection used by researchers is using a Non-Probability Sampling sample type, namely saturated sampling type. The type of research used is a quantitative method with a One Group Pretest-Posttest design type using snake and ladder media. The research instruments and data collection techniques used were observation and documentation sheets. Based on the results of data analysis in the normality test via the Shapiro-Wilk test results, the two variables (PreTest and PostTest) have a statistically normal distribution. The Shapiro-Wilk statistical value for the PreTest is 0.878 with a significance value (p) = 0.066, while for the PostTest it is 0.918 with a significance value (p) = 0.090. Because both p values ​​are greater than 0.05, it can be concluded that the data is normally distributed, thus the hypothesis H0 is rejected and H1 is accepted. So it can be stated that there is a significant influence of the use of snakes and ladders media on mathematical logic intelligence in children aged 5-6 years at One Roof 02 Lubuk Pakam State Kindergarten.